Adaptive capacity of 2- to 5-month-old infants to the flow, shape, and flexibility of different teats during bottle feeding: a cross-sectional study - M. L. J. Lagarde; N. van Alfen; S. A. F. de Groot; A. C. H. Geurts; L. van den Engel-Hoek (BMC, 2019)
Abstract Background Nutritive sucking is a complex activity, the biomechanical components of which may vary in relation to respiratory phase, swallow-rate per minute, suck-swallow ratio, and swallow non-inspiratory flow (SNIF). Quantitative measurement of these components during nutritive sucking in healthy infants could help us to understand the complex development of sucking, swallowing, and breathing. This is important because the coordination between these components is often disturbed in infants with feeding difficulties. The aims of this study were to describe the biomechanical components of sucking and swallowing in healthy 2- to 5-month-old infants during bottle feeding, to assess whether infants adapt to the characteristics of two different teats, and to determine which independent variables influence the occurrence of SNIF. Methods Submental muscle activity, nasal airflow, and cervical auscultation were evaluated during bottle-feeding with two different teats. Results Sixteen term-born infants (6 boys) aged 2-5 months were included. All infants showed variable inhalation and exhalation after swallowing. The swallow rate per minute was significantly higher when infants fed with a higher flow teat (Philips Avent Natural 2.0™). Infants had suck:swallow ratios ranging from 1:1 to 4:1. A suck:swallow ratio of 1:1 occurred significantly more often when infants fed with a higher flow teat, whereas a suck:swallow ratio of 2:1 occurred significantly more often when infants fed with a low-flow teat (Philips Avent Classic+™). A suck:swallow ratio of 1:1 was negatively correlated with SNIF, whereas a suck:swallow ratio of 2:1 was positively correlated with SNIF. Conclusion Healthy infants aged 2-5 months can adapt to the flow, shape, and flexibility of different teats, showing a wide range of biomechanical and motor adaptations.